NMR Study of the Reductive Decomposition of [BMIm][NTf2] at Gold Electrodes and Indirect Electrochemical Conversion of CO2. Issue 16 (20th June 2017) - Michez, Roman; Doneux, Thomas; Buess‐Herman, Claudine; Luhmer, Michel
Abstract: Potential controlled electrolyses of [BMIm][NTf2 ] ionic liquid were performed at a gold cathode under nitrogen atmosphere. The structures of the major conversion products of the BMIm + cation were elucidated on the basis of 1D and 2D nuclear magnetic resonance (NMR) analyses and gas chromatography (GC) analysis of the volatile compounds. Recombination of the imidazol‐2‐yl radicals, generated at the electrode by single electron transfer, leads to neutral diastereomeric dimers in equal proportions, with a faradaic efficiency of 80 %, while disproportionation of these radicals and/or reaction with hydrogen atoms adsorbed at the electrode generates a neutral monomer with 20 % faradaic efficiency. Both pathways also yield the N ‐heterocyclic carbene imidazolin‐2‐ylidene, which is involved in fast proton exchange with the parent BMIm + cation. The reductive decomposition products of the BMIm + cation are no longer detected if the pre‐electrolysed sample is reacted with CO2, which undergoes an indirect reduction and generates the carboxylate adduct. Abstract : Controlled‐potential electrolyses are performed at Au electrodes in [BMIm][NTf2 ] under nitrogen‐saturated conditions. After electrolyses, the formation of carbene, hydrogenated monomers, and neutral dimers are highlighted by NMR spectroscopy. It is found that CO2 is indirectly converted by these electro‐generated products to form imidazolium‐2‐carboxylate.